Micromechanics of CNT grafted FRP based on hierarchical homogenization of transversely isotropic multi-coated model. (October 2019) - Cheng, Yi; Zhang, Kaifu; Liang, Biao; Cheng, Hui; Hou, Guoyi; Xu, Guanhua; Jin, Wei
Highlights: A hierarchical model for effective properties of CNT grafted FRP was conducted. The CNT region was represented by functionally graded interphase around fiber. The composite was modeled as multi-coated model and sequentially homogenized. The effects of volume fraction, modulus and length of CNT were studied. Abstract: Carbon nanotube grafted fiber reinforced polymer possesses promising mechanical properties compared to traditional fiber reinforced composites. A micromechanical model was developed to predict effective properties of the composite in this paper. At first, hierarchical models were conducted to represent CNT region and the whole composite separately. The CNT region was homogenized in micro-scale and regarded as functionally graded interphase surrounding fibers. The whole composite was simulated by a multi-coated model embedded into a transversely isotropic medium in meso‑scale. To solve the multi-coated model, strain concentration tensors for each phase were obtained and incorporated into a sequentially homogenization method. Then the algorithm was implemented using MATLAB software to obtain effective moduli of the composite. The results were verified by FEM simulations and experimental results from existing literatures. In the end, effects of modulus, volume fraction and length of the CNTs on overall properties of the composite were studied.